Skeletal muscle mass loss and dose‐limiting toxicities in metastatic colorectal cancer patients. Issue 4 (15th May 2019) - Kurk, Sophie; Peeters, Petra; Stellato, Rebecca; Dorresteijn, B.; de Jong, Pim; Jourdan, Marion; Creemers, Geert‐Jan; Erdkamp, Frans; de Jongh, Felix; Kint, Peter; Simkens, Lieke; Tanis, Bea; et al.
Abstract: Background: Increasing evidence suggests that severe skeletal muscle index (SMI) loss (sarcopenia) is associated with poor overall survival in metastatic colorectal cancer patients, but its mechanisms are unknown. We recently found, using data of the randomized phase 3 CAIRO3 study, that SMI loss was related with shorter time to disease progression and overall survival during first‐line maintenance treatment with capecitabine + bevacizumab (CAP‐B) or observation and during more intensive capecitabine + oxaliplatin + bevacizumab (CAPOX‐B) reintroduction treatment. As a potential risk factor for reduced survival, we explored whether sarcopenia and SMI loss were associated with dose‐limiting toxicities (DLTs) during CAP‐B and CAPOX‐B. Methods: Sarcopenia status and SMI loss were assessed by using consecutive computed tomography scans. DLTs were defined as any dose delay/reduction/discontinuation of systemic treatment because of reported CTCAE (version 3.0) toxicities at the start or during treatment. Poisson regression models were used to study whether sarcopenia and body mass index (BMI) at the start of treatment and SMI and BMI loss during treatment were associated with DLTs. Results: One hundred eighty‐two patients (mean age 63.0 ± 8.8 years, 37% female) received CAP‐B, and 232 patients (mean age 63.0 ± 9.0 years, 34% female) received CAPOX‐B. At the start of CAP‐B and CAPOX‐B, 54% and 46% of patients were sarcopenic, respectively. Mean BMI was lower in sarcopenic patients, although patients were on average still overweight (sarcopenic vs. non‐sarcopenic at the start of CAP‐B 25.0 ± 3.9 vs. 26.7 ± 4.1 and CAPOX‐B 25.8 ± 3.8 vs. 27.1 ± 3.8 kg/m 2 ). Sarcopenia at the start of CAP‐B was not associated with DLTs [relative risk 0.87 (95% confidence interval 0.64–1.19)], whereas patients with >2% SMI loss had a significantly higher risk of DLTs [1.29 (1.01–1.66)]. At the start of subsequent CAPOX‐B, 25% of patients received a dose reduction, and the risk of dose reduction was significantly higher for patients with preceding SMI loss [1.78 (1.06–3.01)] or sarcopenia [1.75 (1.08–2.86)]. After the received dose reductions, sarcopenia or SMI loss was not significantly associated with a higher risk of DLTs during CAPOX‐B [sarcopenia vs. non‐sarcopenic: 0.86 (0.69–1.08) and SMI loss vs. stable/gain: 0.83 (0.65–1.07)]. In contrast, BMI (loss) at the start or during either treatment was not associated with an increased risk of DLTs. Conclusions: In this large longitudinal study in metastatic colorectal cancer patients during palliative systemic treatment, sarcopenia and/or muscle loss was associated with an increased risk of DLTs. BMI was not associated with DLTs and could not detect sarcopenia or SMI loss. Prospective (randomized) studies should reveal whether normalizing chemotherapeutic doses to muscle mass or muscle mass preservation (by exercise and nutritional interventions) increases chemotherapeutic tolerance and improves survival.